resenha do livro: Studies in the colonial history of Spanish américa - Ferlini, Vera Lúcia do Amaral (Revista de História, 2023)
Resenha do livro:GÓNGORA, Mario. Studies in the colonial history of spanish América. Transl. Richard Southern. London: Cambridge University Press, 1975, 239p. (Cambridge Latin American Studies 20)